2011
DOI: 10.5352/jls.2011.21.8.1176
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moderate Exercise Training on Splenocyte Inflammatory Cytokine Production in High Fat Diet Induced Obese Mice

Abstract: The present research was conducted to investigate the effect of moderate exercise training on splenocyte inflammatory cytokines production in high fat diet-induced obese mice. To determine the effects of exercise training and low fat diet on splenocyte, C57BL/6 male mice (4 weeks aged, n=20) were fed a high fat diet (45% fat diet) for 5 weeks so that obesity was achieved intentionally. These obese mice were then divided into 2 groups; HLC (low fat diet and control n=10), and HLE (low fat diet and exercise n=10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
1
2
0
1
Order By: Relevance
“…Such result was the same with the weight reduction and according to previous studies [ 9 , 17 ] where expression of proinflammatory cytokine and weight are closely related and thus demonstrated that there is a correlation between weight reduction and expression decrease of inflammatory cytokine.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Such result was the same with the weight reduction and according to previous studies [ 9 , 17 ] where expression of proinflammatory cytokine and weight are closely related and thus demonstrated that there is a correlation between weight reduction and expression decrease of inflammatory cytokine.…”
Section: Discussionsupporting
confidence: 89%
“…Conducting medium strength exercises brings positive effects of proinflammatory cytokine decrease, which was expressed from immune cells, and immunity increase in the obese model [ 9 , 10 ] and even with moderate one-off exercise alone, chemotaxis increase of macrophage [ 11 ] and significant results on lymphocyte proliferation response and antigen-specific immune response, which were gained upon the completion of mitogen stimulation with antigen, were achieved [ 12 ], but high-intensity one-off exercise or exhaustive exercise was reported to negatively affect immunity by increasing contagiosity [ 13 ] and proinflammatory cytokine such as IL-6 and IL-1ra and thus the results are contradictory based on exercise intensity or the duration of exercise.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, most cytokines are known to decrease after a high-intensity exercise [25]. Some prior studies suggest that cytokine gene expression increases during recovery after a high-intensity exercise and/or no difference in the amount of cytokines in the spleen after a high-intensity exercise [26,27]. Thus, the increase in IL-4 and IL-6 mRNA expansion in the spleen, unlike the cytokine in the blood, is thought to change during recovery after a high-intensity exercise.…”
Section: Discussionmentioning
confidence: 99%
“…운동과 관련된 선생연구를 고찰해보면, 고지방 식이로 비 만을 유도한 동물을 이용하여 저지방식이와 운동의 복합처 치는 IL-6와 TNF-α와 같은 염증성 싸이토카인의 발현이 감소 된 것으로 보고하였고 (Chang et al, 2011), 또 다른 연구에서 는 중강도의 유산소 운동이 PGC1-α의 활성도를 증가시켜 전 사인자인 Tfam등의 활성을 증가시키는 것으로 보고하였다 (Benton et al, 2006). (Manach et al, 2004).…”
Section: ⅰ 서론unclassified